2015
DOI: 10.1038/srep10174
|View full text |Cite
|
Sign up to set email alerts
|

Three Temperature Regimes in Superconducting Photon Detectors: Quantum, Thermal and Multiple Phase-Slips as Generators of Dark Counts

Abstract: We perform measurements of the switching current distributions of three w ≈ 120 nm wide, 4 nm thick NbN superconducting strips which are used for single-photon detectors. These strips are much wider than the diameter of the vortex cores, so they are classified as quasi-two-dimensional (quasi-2D). We discover evidence of macroscopic quantum tunneling by observing the saturation of the standard deviation of the switching distributions at temperatures around 2 K. We analyze our results using the Kurkijärvi-Garg m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 46 publications
(92 reference statements)
2
17
1
Order By: Relevance
“…Murphy et al . 12 has recently investigated “[…] quantum, thermal and multiple phase slips as generators of dark counts” in quasi-2D NbN strips.…”
Section: Introductionmentioning
confidence: 99%
“…Murphy et al . 12 has recently investigated “[…] quantum, thermal and multiple phase slips as generators of dark counts” in quasi-2D NbN strips.…”
Section: Introductionmentioning
confidence: 99%
“…We take t = 0.2 and   At finite current, the measured sheet resistance is several orders of magnitude larger than the theory would suggest. Typical dark count rates in similar nanowires at 1.5 K are ~10 2 -10 4 Hz, 17 with each dark count corresponding to the creation of a resistive region with a resistance of ≈ 6 k for a duration of ≈0.25 ns. 18 The resulting time-average resistance due to dark counts is too low to explain the observed behavior.…”
Section: B Current Dependencementioning
confidence: 99%
“…A temperature-dependent study [69] revealed a growing inconsistency between theory and experiment at temperatures below ≈ 2.5 K ¶. Very recently, the switching current distributions as a function of temperature in typical meander structures as used for SNSPD have been measured [70]. A detailed statistical analysis suggests that at temperatures T 2 K dark counts may not be thermally activated, but caused by quantum-mechanical tunneling events, so called QPS.…”
Section: Dark Countsmentioning
confidence: 99%